Description of Kingella potus sp. nov., an Organism Isolated from a Wound Caused by an Animal Bite - Lawson, Paul A.; Malnick, Henry; Collins, Matthew D.; Shah, Jayesh J.; Chattaway, Marie A.; Bendall, Richard; Hartley, John W. (My University, 2005)
We report the isolation and characterization of a hitherto unknown gram-negative, rod-shaped Neisseria-like organism from an infected wound resulting from a bite from a kinkajou. Based on both phenotypic and phylogenetic evidence, it is proposed that the unknown organism be classified as a new species, Kingella potus sp. nov.
Keywords: Biology, Microbiology.